Environmental-Genetic Interactions in the Pathogenesis of Parkinson's Disease - Tsuboi, Yoshio (The Korean Society for Brain and Neural Science, 2012)
To date, numerous case-control studies have shown the complexity of the pathogenesis of Parkinson's disease (PD). In terms of genetic factors, several susceptibility genes are known to contribute to the development of PD, including α-synuclein (SNCA), leucine-rich repeat kinase 2 (LRRK2), and glucocerebrosidase (GBA). In addition, numerous recent epidemiological studies have shown that several environmental factors are either risk factors for PD or protective factors against PD. Risk factors identified include herbicides and pesticides (e.g., paraquat, rotenone, and maneb), metals (e.g., manganese and lead), head trauma, and well water. In contrast, smoking and coffee/caffeine consumption are known to be protective against PD. A recent finding in this field is that environmental-genetic interactions contribute more to the pathogenesis of PD than do genetic factors or environmental factors alone. In this review, I will discuss how these interactions promote the development of PD.